IDENTIFICATION AND CHARACTERIZATION OF LACTOCOCCUS GARVIEAE AND ANTIMICROBIAL ACTIVITY OF ITS BACTERIOCIN ISOLATED FROM COW’S MILK - SUNEEL, DODAMANI; KALIWAL BASAPPA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
This study was conducted to isolate lactic acid bacteria (LAB) from cow's milk and characterize through morphological, physiological, biochemical, carbohydrate fermentation and its antimicrobial property. The bacteria were isolated by serial dilution of milk samples and confirmed through biochemical, physiological and 16s rRNA sequencing. The antibiotic susceptibility test of bacteria, antimicrobial test of bacteriocin by agar well diffusion assay was carried out. A total of 12 LAB has been isolated among them one isolate which showed good antimicrobial activity against Gram-positive bacteria viz., Staphylococcus aureus, Bacillus subtilis and Bacillus cereus and gram-negative bacteria viz., Pseudomonas aeruginosa and E.coli was chosen for further analysis.Â The gram +ve LAB grew well at pH 5 and 7, at temperature 25 and 37â—¦C, 5% Nacl solution and no growth was observed at pH 4 and 9, at temperature 4 and 45â—¦C, 15 and 25 % Nacl concentration. The LAB was catalase, gelatin and oxidase â€“ve and non acid fast. Further, through 16s rRNA gene sequencing it was identified as Lactococcus garvieae The study showed that the Lactococcus garvieae produce bacteriocin that inhibits a wide variety of pathogenic microbes which suggested that it can be used as an alternative type of antibiotic. Keywords: Lactococcus garvieae, Bacteriocin, Antimicrobial susceptibility, Milk